The associations between mixed blood heavy metal exposure and depressive symptom: a cross-sectional study in Shandong, China - Jing Hou; Yi He; Haifeng Lian; Haosen Yan; Jialian Li; Lailai Yan; Wenzhong Huang; Yiwen Zhang; Sen Gao; Hongwei Sun; Peng Lu (BMC Public Health)
Abstract Background Given the limited research on the effects of heavy metals on depressive symptoms in young adults and the high prevalence of depression within this age group, it is essential to investigate the potential impact of heavy metals on depressive symptoms. Methods This study involved 2027 college students from Shandong, China. Blood concentrations of heavy metals were measured, and depressive symptoms were assessed using the Patient Health Questionnaire-9 (PHQ-9). The Environmental Risk Score (ERS) was used to analyze the relationship between mixed blood heavy metal exposure and depressive symptoms. Sensitivity analyses were conducted using Bayesian Kernel Machine Regression (BKMR) and quantile g-computation (qgcomp) to explore the mixing effect of heavy metals. Results A significant positive association was found between ERS and the risk of depressive symptoms. The main effects of silver (Ag), antimony (Sb), tin (Sn), lanthanum (La), and cerium (Ce) were also positively associated with depressive symptoms. Notably, Ce showed an inverted “U”-shaped nonlinear relationship with depressive symptoms risk. La and Ce exhibited antagonistic effects on the increased risk. Conclusion In summary, mixed exposure to these five metals may be on the relationship between heavy metal exposure and depressive symptoms in young adults.